2011
DOI: 10.2196/jmir.1840
|View full text |Cite
|
Sign up to set email alerts
|

Does the eHealth Literacy Scale (eHEALS) Measure What it Intends to Measure? Validation of a Dutch Version of the eHEALS in Two Adult Populations

Abstract: BackgroundThe Internet increases the availability of health information, which consequently expands the amount of skills that health care consumers must have to obtain and evaluate health information. Norman and Skinner in 2006 developed an 8-item self-report eHealth literacy scale to measure these skills: the eHealth Literacy Scale (eHEALS). This instrument has been available only in English and there are no data on its validity.ObjectivesThe objective of our study was to assess the internal consistency and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
376
7
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(414 citation statements)
references
References 36 publications
23
376
7
8
Order By: Relevance
“…eHEALS is a patientreported tool and it has been identified that people tend to overestimate their computer skills, which can create a discrepancy between self-reported skills and actual skills [21]. In this sense, our study is limited t o self-perceived eHealth literacy and studies of actual eHealth literacy are still needed for lung cancer survivors.…”
Section: Discussionmentioning
confidence: 95%
“…eHEALS is a patientreported tool and it has been identified that people tend to overestimate their computer skills, which can create a discrepancy between self-reported skills and actual skills [21]. In this sense, our study is limited t o self-perceived eHealth literacy and studies of actual eHealth literacy are still needed for lung cancer survivors.…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, there has been some recent research questioning the validity of the eHEALS tool use in various populations (Chan and Kaufman 2011;Stellefson et al 2011;van der Vaart et al 2011), with the inherent changing nature of the Internet and the purpose and context of the eHEALS for this use. Norman (2012), co-developer of the eHEALS survey, highlights that despite a changing context of health information, the fundamental skills of eHealth literacy have not changed.…”
Section: Limitationsmentioning
confidence: 99%
“…The inadequacy of existing health literacy assessment tools has been pointed out by many researchers [11,58-61]. In addition, there are few assessments of any type that focus specifically on the health literacy of adolescents [6,11,62,63].…”
Section: Introductionmentioning
confidence: 99%